Urban environments harbor greater oomycete and Phytophthora diversity, creating a bridgehead for potential new pathogens to natural ecosystems. Issue 5 (22nd April 2022) - Dale, Angela L.; Feau, Nicolas; Berube, Jean A.; Ponchart, Julien; Bilodeau, Guillaume J.; Hamelin, Richard C.
Abstract: Anthropogenic activities contribute to changes in the range and distribution of species. Globalization is resulting in human‐mediated dispersal that is causing a breakdown in normal biogeographic barriers. But the impact of anthropogenic activities on plant pathogen communities is still poorly understood. We conducted an eDNA metabarcoding study to compare communities of oomycetes, a group of eukaryotic microorganisms that comprises important crop and tree pathogens, in urban, natural, and interface environments. Oomycete diversity and abundance were highest in human impacted urban environments and lowest in natural environments, while the interface environments were intermediate. Urban environments had the highest proportion of sites where species of the plant pathogenic genus Phytophthora were found, as well as the largest number of unknown or undescribed Phytophthora species. The taxa overlap between urban and interface environments was one order of magnitude larger than the overlap between urban and natural environments. Our analyses show that urban/natural interface areas likely act as a bridge for invasion into natural environments. This could impact both the natural biota and natural ecosystem processes. Our study serves as a warning that some Phytophthora species introduced from nurseries or spread by human movement could pose a threat to natural ecosystems. Shifting patterns in oomycete communities could interfere with natural ecosystem processes and result in increases in disease and ecosystem declines. Abstract : Globalization is responsible for the transmission of pathogens across geographic areas, which often results in deadly forest disease outbreaks, such as the Dutch elm disease and the sudden oak death. We conducted an eDNA metabarcoding study on soil and water samples from urban, natural forests, and interface sites and discovered that urban environments have the highest diversity of oomycetes and Phytophthora, a particularly deathly group of pathogens, and more undescribed taxa, compared to natural forests. Urban and interface environments likely play an important role in spreading invasive species to natural forests.